Inter-rater reliability of a video-analysis method measuring low-back load inafield situation - Coenen, Pieter; Kingma, I.; Boot, C.; Bongers, P.; Van Dieën, J. (2013)
Valid and reliable low-back load assessment tools that can be used in field situations are needed for epidemiologic studies and for ergonomic practice. The aim of this study was to assess the inter-rater reliability of a low-back load video-analysis method in a field setting.Five raters analyzed 50 work site manual material handling tasks of 14 workers. Peak and mean moments at the level of L5S1, and segment angles were obtained using the video-analysis method. Intra-class correlation coefficients (ICCs) and median standard deviations across raters were calculated.ICCs revealed excellent inter-rater reliability (>0.9) for peak and mean moments, ICCs of segment angles were variable. Median standard deviations showed relatively small inter-rater variance for moments (standard deviation <10Nm) and segment angle variation ranging from 0° to 20°. The proposed video-analysis method, provides a reliable tool for obtaining low-back loads from occupational field tasks. © 2013 Elsevier Ltd and The Ergonomics Society.